BOOK REVIEW: EMERGING TRENDS OF ICT IN TEACHING AND LEARNING: ICT IN ENGLISH LANGUAGE TEACHING - Isma, Adi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
The book “Emerging Trends of ICT in Teaching and Learning” is edited by (N.Devaki M.Deivam, 2022). It aims to provide insight into the latest trends in Information and Communications Technology (ICT) and their influence on social, cultural, and economic spheres, with a specific focus on teaching and learning. It caters to teachers, students, and researchers who focus on ICT-related courses, while other researchers can take it as a convenient reference. The objective of the book is to bring together the tools, techniques, and strategies of seasoned researchers in one volume, enabling readers to develop top-quality literature on ICT. The chapters of this book cover various topics such as cyber security, digital initiatives, ICT for English language teaching, web-based learning, smart classrooms, and technological tools. However, the focus of this review is on the chapters that discuss ICT for English language teaching and learning.